Aquablation for benign prostatic hyperplasia in large prostates (80–150 mL): 6‐month results from the WATER II trial. (29th March 2019) - Desai, Mihir; Bidair, Mo; Zorn, Kevin C.; Trainer, Andrew; Arther, Andrew; Kramolowsky, Eugene; Doumanian, Leo; Elterman, Dean; Kaufman, Ronald P.; Lingeman, James; Krambeck, Amy; Eure, Gregg; et al.
Abstract : Objective: To present 6‐month safety and effectiveness data from a multicentre prospective study of aquablation in men with lower urinary tract symptoms (LUTS) attributable to benign prostatic hyperplasia (BPH) with prostate volumes between 80 and 150 mL. Methods: Between September and December 2017, 101 men with LUTSattributable to BPHwere prospectively enrolled at 16 centres in Canada and the USA. Results: The mean prostate volume was 107 mL. The mean length of hospital stay after the aquablation procedure was 1.6 days (range: same day to 6 days). The primary safety endpoint (Clavien–Dindo grade 2 or higher or any grade 1 event resulting in persistent disability) at 3 months occurred in 45.5% of men, which met the study design goal of < 65% ( P < 0.001). At 6 months, 22% of the patients had experienced a Clavien–Dindo grade 2, 14% a grade 3 and 5% a grade 4 adverse event. Bleeding complications requiring intervention and/or transfusion were recorded in eight patients prior to discharge and in six patients after discharge. The mean International Prostate Symptom Score improved from 23.2 ± 6.3 at baseline to 6.7 ± 5.1 at 3 months, meeting the study's primary efficacy endpoint goal ( P < 0.001). The maximum urinary flow rate increased from 8.7 to 18.8 mL/s ( P < 0.001) and post‐void residual urine volume decreased from 131 at baseline to 47 at 6 months ( P < 0.0001). At 6 months, prostate‐specific antigen concentration reduced from 7.1 ± 5.9 ng/mL at baseline to 4.0 ± 3.9 ng/mL, a 44% reduction. Conclusions: Aquablation is safe and effective in treating men with larger prostates (80–150 mL), without significant increase in procedure or resection time.